Moral Values ​​in the Film The Lion King and Its Relevance for Strengthening Character Education of Elementary School Students: Nilai-Nilai Moral dalam Film The Lion King dan Relevansinya untuk Penguatan Pendidikan Karakter Siswa Sekolah Dasar - Ratih Oktafiani Alda Intansari; Supriyadi Supriyadi (Universitas Muhammadiyah Sidoarjo, 2021)
Elementary school children tend to have very diverse interests. One of them is watching cartoons from television shows or YouTube. Elementary school-age children tend to enter a phase of imitating what they see, hear and feel. This is very important for all parents to pay attention to, because the movies they watch can affect the character or personality of the child. This study aims to determine the moral values ​​in the lion king film for elementary school children that can be used as character reinforcement. This research uses a qualitative approach with a narrative study type of research that analyzes the content of the lion king film. The way to analyze the data in this study is by playing the film, then recording the contents of the lion king film and transferring the results of the notes to the form of dialogue between characters which shows the existence of moral values ​​that can be used as character strengthening. The results of this study found that there were eleven moral values ​​in accordance with Thomas Lickona's (1991) theory of knowing goodness, doing good, and loving kindness. In addition, these moral values ​​also have relevance to character strengthening in accordance with the 2017 Ministry of Education and Culture regulations. The impact of the lion king film itself is expected to strengthen children's character and develop motivation in children's activities in their daily lives. It can be seen that the lion king film has moral values ​​that should be imitated by elementary school children.